1993
DOI: 10.1002/pro.5560021224
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interaction of RNA polymerase II with nucleosomes. II. During read‐through and elongation

Abstract: The sulfhydryl-specific fluorescence probe 1,SIAEDANS (5-(2-((iodoacetyl)amino)ethyl)amino-naphthalene-1-sulfonic acid) was attached to the single cysteine of H3, and reconstituted fluorescent mononucleosomes were used as the template for in vitro transcription by the yeast RNA polymerase I1 (pol 11). DNase 1 digestion analysis revealed that transcription of nucleosomes by pol I1 resulted in an overall loosening of the structure. Monitoring the transcription event by steady-state fluorescence analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…However, this new conformation may be energetically unfavorable, reverting back to the original state the moment pol I1 leaves the nucleosome. This hypothesis is further substantiated by results reported in the accompanying paper (Bhargava, 1993).…”
Section: Binding Of Pol I1 To Nucleosomes Results In a More Compact Ssupporting
confidence: 75%
See 2 more Smart Citations
“…However, this new conformation may be energetically unfavorable, reverting back to the original state the moment pol I1 leaves the nucleosome. This hypothesis is further substantiated by results reported in the accompanying paper (Bhargava, 1993).…”
Section: Binding Of Pol I1 To Nucleosomes Results In a More Compact Ssupporting
confidence: 75%
“…Fluorescence titration data demonstrated a molar stoichiometry of 1: 1 for the binding of nucleosomes and pol 11, and an in vitro transcript size equal to the size of the template DNA (Bhargava, 1993) suggested read through from one end of the template to the other. Therefore, it was concluded that nucleosome and pol I1 probably form a high-affinity complex with 1 : 1 molar stoichiometry.…”
Section: Binding and Transcription Of Nucleosomes By Pol II Is Facilimentioning
confidence: 98%
See 1 more Smart Citation
“…Histone replacement/exchange by RI assembly on transcribed templates suggests a possible mechanism for read‐through of a nucleosomal template by the enzyme RNA polymerase. It was found in an in vitro study that RNA polymerase II (pol II) can transcribe through a nucleosome without completely displacing histones from it [87]. The protein complex facilitates chromatin transcription (FACT) facilitates read‐through of the nucleosomal template by RNA polymerase II during transcription elongation [88].…”
Section: Variants Of Core Histones In Various Nuclear Processesmentioning
confidence: 99%
“…It is generally considered repressive for gene expression as wrapping of DNA into nucleosomes may block the accessibility of the promoter sequences. Nevertheless, RNA polymerase can read through a nucleosome, which can also promote the interaction between two DNA‐binding proteins by bringing them closer together in space 55, 56. Thus, it is established now that the relative positions of the nucleosomes with reference to the underlying DNA sequences of the genome have a profound effect on the activity status of the genome.…”
Section: Nucleosome Positioning and Chromatin Dynamics In Gene Regumentioning
confidence: 99%